Application of Tamarindus indica seed extract as bio-coagulant to removal suspended solids and colors - Agustin Dewi; Iva Rustanti Eri; Hermiyanti Pratiwi; Nerawati Diana A.T; Narwati Narwati (Intelektual Pustaka Media Utama, 2021)
The batik traditional industries in East Java, Indonesia generally not have a proper wastewater treatment plant yet, so liquid waste directly discharge into the river. Batik wastewater generally have a dark color, which derived from the coloring of naphthol with number of suspended solids greater than 100 mg/L and color concentration more than 250 Pt.Co. Tamarind seed extract is known to contain natural polyelectrolytes active group, which had function as bio-coagulant. The research objective was to analyze the application of tamarind seed extract as bio-coagulant in wastewater treatment of the Batik traditional industries, by reducing suspended solids levels and color of wastewater. The research design used pretest and posttest control group design with variations of bio-coagulant doses of 10ml/L, 30ml/L, and 50ml/L, and analyzed using the Two Way Anova Test. The results showed that the level of suspended solids in wastewater before treatment averaged 291mg/L, and the average color content was 593 Pt-Co, so it did not meet the quality standards of the Governor of East Java No 72/2013. For the highest reduction in suspended solids levels at a dose of 10ml/L reduced up to 95.1% and the highest decrease in color levels at a dose of 50ml/L, reduced up to 87.8%. Traditional batik wastewater treatment, which used a coagulation-flocculation process with bio-coagulant extract of tamarind seeds could reduce levels of suspended solids and colors, in order to meet the specified quality standards.